2021
DOI: 10.3758/s13428-021-01602-9
|View full text |Cite
|
Sign up to set email alerts
|

Building an intelligent recommendation system for personalized test scheduling in computerized assessments: A reinforcement learning approach

Abstract: The introduction of computerized formative assessments in the classroom has opened a new area of effective progress monitoring with more accessible test administrations. With computerized formative assessments, all students could be tested at the same time and with the same number of test administrations within a school year. Alternatively, the decision for the number and frequency of such tests could be made by teachers based on their observations and personal judgments about students. However, this often res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The authors found that recommender system techniques such as matrix factorization and collaborative filtering outperformed the traditional regression methods in predicting student performance. Recently, more advanced algorithms and approaches such as reinforcement learning [11,19] have been proposed to improve the capacity, architectural flexibility, and performance accuracy of the recommender systems adopted within educational contexts.…”
Section: Recommender Systems For Educational Assessmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors found that recommender system techniques such as matrix factorization and collaborative filtering outperformed the traditional regression methods in predicting student performance. Recently, more advanced algorithms and approaches such as reinforcement learning [11,19] have been proposed to improve the capacity, architectural flexibility, and performance accuracy of the recommender systems adopted within educational contexts.…”
Section: Recommender Systems For Educational Assessmentsmentioning
confidence: 99%
“…The findings of their study indicated that the IRS could yield a significant reduction in the total number of test administrations required to make accurate decisions on students' academic growth. Similarly, Shin and Bulut [11] also proposed a recommender system using a reinforcement learning algorithm that aimed to optimize test administration schedules for students. The proposed system could identify the critical time points for students to demonstrate their academic growth.…”
Section: Recommender Systems For Educational Assessmentsmentioning
confidence: 99%
See 3 more Smart Citations